Liver abscess and septic shock due to Clostridium perfringens infection: a case report and literature review - Yu, Fangyu; Guo, Yuxin; Li, Yujiao; Gai, Wei; Zhang, Qianping; Li, Pochen; Xu, Ruyi; Zhang, Lingyao; Zheng, Yafeng; Zhang, Xiaojing (Frontiers in Medicine, 2025)
Clostridium perfringens causes liver abscesses with a low incidence, rapid progression, and high mortality. Within a few days or even within 24 h, patients may progress from a liver abscess to sepsis, multi-organ failure, and potentially death. Diagnosing Clostridium perfringens infection by routine microbiological testing (CMT) is often challenging. Here, we present a patient with negative blood cultures who was ultimately diagnosed with a liver abscess due to Clostridium perfringens infection, confirmed by metagenomic next-generation sequencing (mNGS). The patient initially presented with fever only, and his blood cultures were negative. Subsequently, the patient’s condition progressed rapidly, and he developed signs of septic shock. Immediately after admission to the ICU, he received combined anti-infective therapy with meropenem and tigecycline, as well as urgent ultrasound-guided puncture and drainage. Blood mNGS identified Clostridium perfringens and a variety of anaerobic bacteria, confirming that the pathogen had been covered by empirical antibiotics. Continued anti-infective therapy and drainage improved the patient’s symptoms, and he was eventually discharged from the hospital. Clinicians should be highly suspicious of liver abscesses with negative blood cultures. The use of mNGS to identify the pathogen, appropriate antibiotics, and abscess aspiration and drainage are key to patient survival.